ANALISIS STRATEGI DIGITAL MARKETING DAN FENOMENA FEAR OF MISSING OUT (FOMO) TERHADAP PERMINTAAN KONSUMEN MINUMAN BOBA: STUDI KASUS CHATIME - Najwa Nur Kamila; Indah Yuli Kustianah; Helena Maniku; Kamilah Maryza (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study aims to analyze the role of Fear of Missing Out (FOMO) and digital marketing strategies on consumer demand in the bubble tea industry, with Chatime as the case study. The research employed a descriptive qualitative method through observations and interviews, supported by secondary data collected from journals, articles, and related publications. The findings indicate that FOMO and digital marketing strategies implemented through social media, particularly TikTok and Instagram, influence consumer interest and purchasing decisions. Digital promotions in the form of vouchers, engaging visual content, and influencer endorsements were found to increase product demand. The data show that 50% of transactions in January 2025 were generated through TikTok vouchers, indicating the strong influence of digital promotions on consumer behavior. However, demand remains fluctuating due to changes in social media trends and market competition. Therefore, the utilization of FOMO and digital marketing can effectively increase consumer demand in the short term, but long-term business sustainability requires product innovation, customer loyalty programs, and adaptability to changing market trends.